10 Prehospital critical care team attendance increases the survival of major trauma patients: national registry data. (21st May 2017) - Maddock, A; Corfield, A; Donald, M; Hearns, S; Lyon, R; Fitzpatrick, D; Sinclair, N
Abstract : Aim: To investigate the effect of prehospital critical care team attendance, versus usual ambulance care, on trauma patient mortality. Methods: We retrospectively examined data from the Scottish Trauma Audit Group for the calendar years 2011–14, covering all trauma patients admitted to hospital in Scotland. We divided them into two groups: those who were seen by a prehospital critical care team; and those who received standard ambulance care only. We compared expected mortality (by TRISS and PS12 models) with observed mortality within each group, with subanalysis of major trauma patients (Injury Severity Score >15). Results: 10 252 patients were available for analysis. Of these, 503 (4.9%) were seen by a prehospital critical care team and 9749 (95.1%) received standard ambulance care. There was a non significant increase in excess survivors (0.9/100 patients) in the group who received critical care (p=0.58). 1545 major trauma patients were available for analysis. Of these, 210 (13.6%) were seen by a prehospital critical care team and 1335 (86.4%) received standard ambulance care. There was a significant increase in excess survivors (4.5/100 patients) in major trauma patients who received critical care (p=0.03). Conclusion: In major trauma patients in Scotland, the addition of prehospital critical care to standard ambulance care results in an increase in patient survival. This study adds to the growing body of evidence supporting the utility of prehospital critical care, especially in the most severely injured patients. Conflict of interest: None declared. Funding: None declared.